A New Cryptographic Strategy for Digital Images - Nidhi Sethi; Sandip Vijay (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In this paper, a new image block cipher encryption strategy for gray scale images using a different set of secret key and sizes is proposed. Initially, the swapping and dispersion is done without keys and in second stage the image is mixed with the chirikov map involving first secret key.  'N' rounds are taken to complete this process. The blended image is divided into blocks of block size 8X8.These blocks are also swapped to achieve good confusion. For making the encryption scheme more sturdy in each block the transmutation of pixels is done with the modified logistic map having three more secret keys.  The proposed scheme is simple, rapid and sensitive to the secret key. Due to the high order of substitution, common attacks such as linear and differential cryptanalysis are unattainable. The experimental results show that the proposed encryption technique is effective and has high security features.DOI:http://dx.doi.org/10.11591/ijece.v4i3.6325